2019
DOI: 10.1177/0960327119871095
|View full text |Cite
|
Sign up to set email alerts
|

Hepatorenal protective effects of protocatechuic acid in rats administered with anticancer drug methotrexate

Abstract: The efficacy of methotrexate (MTX) as an anticancer drug is limited by some adverse effects including hepatic and renal toxicities. The present study investigated the possible protective effect of protocatechuic acid (PCA), a phenolic phytochemical widely present in several edible vegetables and fruits, on hepatorenal toxicity associated with MTX treatment in rats. Male Wistar rats were randomly assigned to five groups ( n = 10), namely control, MTX alone (20 mg/kg), PCA alone (50 mg/kg), and rats tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 45 publications
3
19
0
Order By: Relevance
“…Previous investigations found that PCA inhibited lipid peroxidation under different conditions, such as renal damage following doxorubicin treatment (Molehin et al, 2019) and murine diabetic model (Adedara et al, 2019). PCA exerts its antioxidant properties through mitigation of free radicals, activation of the Nrf-2 pathway, and reinforcement of GSH and its dependent enzyme activities (Cheng et al, 2019;Owumi, Ajijola, et al, 2019;Owumi, Ochaoga, et al, 2019). In addition, the phenolic hydroxyl groups present in PCA are correlated to the activation of endogenous antioxidant enzymes (Han et al, 2018).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous investigations found that PCA inhibited lipid peroxidation under different conditions, such as renal damage following doxorubicin treatment (Molehin et al, 2019) and murine diabetic model (Adedara et al, 2019). PCA exerts its antioxidant properties through mitigation of free radicals, activation of the Nrf-2 pathway, and reinforcement of GSH and its dependent enzyme activities (Cheng et al, 2019;Owumi, Ajijola, et al, 2019;Owumi, Ochaoga, et al, 2019). In addition, the phenolic hydroxyl groups present in PCA are correlated to the activation of endogenous antioxidant enzymes (Han et al, 2018).…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies using different animal models have demonstrated the anti-inflammatory potential of PCA (Al Olayan et al, 2020;Owumi, Ajijola, et al, 2019;Owumi, Ochaoga, et al, 2019). In addition, Wang et al (2015) showed that PCA treatment blocks NF-κB activation through enhancement of peroxisome proliferator-activated receptor-gamma in human gingival fibroblasts.…”
Section: F I G U R Ementioning
confidence: 94%
“…The chemoprotective effect of various polyphenolic compounds has been widely reported [ 29‐33 ] against cellular injury. Polyphenol confers protective benefits against chemical damage to cells, [ 34‐36 ] disease onsets such as cancer, [ 37,38 ] and neurological syndromes.…”
Section: Introductionmentioning
confidence: 99%
“…The activities of testicular and epididymal myeloperoxidase (MPO) were evaluated by the modified method described by Trush et al., and as previously reported (Owumi et al., 2019; Trush et al., 1994), MPO catalyses the oxidation of O ‐dianisidine in the presence of H 2 O 2 to yield a brown colour that absorbs maximally at 460 nm. The combined solutions of buffered O ‐dianisidine and H 2 O 2 (200 µl) were incubated with an aliquot of the tissue homogenate sample (7 µl) in specified wells of a microplate.…”
Section: Methodsmentioning
confidence: 99%